Alterations of the CIB2 calcium- and integrin-binding protein cause Usher syndrome type 1J and nonsyndromic deafness DFNB48. - Riazuddin, S.; Belyantseva, I.A.; Giese, A.P.; Lee, K.; Indzhykulian, A.A.; Nandamuri, S.P.; Yousaf, R.; Sinha, G.P.; Lee, S.; Terrell, D.; Hegde, R.S.; Ali, R.A.; et al. (Nature Genetics, 2012)
Sensorineural hearing loss is genetically heterogeneous. Here, we report that mutations in CIB2, which encodes a calcium- and integrin-binding protein, are associated with nonsyndromic deafness (DFNB48) and Usher syndrome type 1J (USH1J). One mutation in CIB2 is a prevalent cause of deafness DFNB48 in Pakistan; other CIB2 mutations contribute to deafness elsewhere in the world. In mice, CIB2 is localized to the mechanosensory stereocilia of inner ear hair cells and to retinal photoreceptor and pigmented epithelium cells. Consistent with molecular modeling predictions of calcium binding, CIB2 significantly decreased the ATP-induced calcium responses in heterologous cells, whereas mutations in deafness DFNB48 altered CIB2 effects on calcium responses. Furthermore, in zebrafish and Drosophila melanogaster, CIB2 is essential for the function and proper development of hair cells and retinal photoreceptor cells. We also show that CIB2 is a new member of the vertebrate Usher interactome.